Analisis Bauran Pemasaran Usaha Makanan Tradisional Studi Kasus Usaha Rengginang Ibu Sisu di Sidodadi Kecamatan Kinali - Lusia Rohima; Cahya Agung Mulyana (ARZUSIN, 2026)
Marketing mix analysis in traditional food businesses has become a focus in various previous studies, but research that specifically discusses the implementation of marketing strategies in MSME-scale rengginang businesses in Sidodadi, Kinali Subdistrict, remains limited. This study aims to analyze the implementation of the marketing mix and its role in the sustainability and development of Mrs. Sisu’s rengginang business in Sidodadi, Kinali Subdistrict. This study employed a qualitative approach with a case study design. The main informant of the study was the business owner, selected through the purposive sampling technique. Data were collected through interviews, observations, and documentation and were then analyzed using qualitative descriptive analysis techniques. The results show that the implementation of the marketing mix, which includes product, price, place, and promotion, has not been carried out optimally, particularly in the aspects of promotion and the use of digital technology. The rengginang product has good quality and continues to maintain its traditional taste, but pricing and distribution strategies are still limited to the local market. The promotion aspect is the main weakness because digital media have not been utilized optimally. These findings contribute to the development of marketing studies, particularly the concept of the marketing mix in the context of traditional food MSMEs, and broaden understanding of small business adaptation strategies amid market changes. The conclusion of the study emphasizes the importance of optimizing the marketing mix to improve business competitiveness. The practical implication is that MSME actors need to improve digital-based promotional innovation, while the government can strengthen support for the development of traditional food businesses through marketing assistance and expanded market access.